Peran Ibu dalam Pengembangan Kecerdasan Matematis-Logis Anak Usia Dini - Warnidah Warnidah (AN-NISA, 2018)
Logical-mathematical intelligence is an intelligence that needs to be developed in children. This becomes necessary because logical mathematical intelligence has a framework that combines the mathematical and logical sides that become a model for developing children's intelligence which is seen as appropriate for the child's development. In its implementation, mothers have a strategic role given their intense interaction with early childhood.